(3GdTLQI hGdaUhds - (3YHO GdSdGe Hf CMeO Hf ZGfe GdfGHdSj GdebOSj, YR GdOjf,J (B678 (3g` s
(3ChdgG (B:s
(3hHYO aEfi fXQJ Edi Gdchf hJchjfg hEdi Gddhf hJdhjfg aQCjJ Gdchf cdg TQLI CUd HPQgG ef MHI s
(3BNQgG (B:s
(3hjCcd CQGjL GdJhcd , aHefY ef OHjH Sehe Edi GdbdH hjOaY YahfI GdQYhfI Je cJGH GdTLQI hGdaUhd ai GdhYX s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B355 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B223 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B5 - (3U (B571s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JUha Mdje (B177) s
Keywords: (3GdJhMjO hGdedd hGdfMds